Pengujian Kinerja Pendinginan Thermo Electic Cooling ( TEC) Menggunakan Heatsink Dengan Variasi Dimensi dan Jenis Material - Muhammad Akbar; Teuku Azuar Rizal; Rita Syntia (Fakultas Teknik Universitas Samudra, 2021)
A thermoelectric generator is an electrical generator device that converts heat energy into electricity directly based on the Seebeck effect method, namely if two different metals are connected at one end, then given a different temperature at the connection, there will be a voltage difference at the other end. with the other end, this study uses peltier tec-12706, the purpose of this study is to determine the effect of the temperature difference between the cold side and the hot side of the varied heatsink/fin designs. This thermoelectric component is coated by a thin ceramic that contains a bismuth telluride rod inside. When in supply the dc voltage is 12volt-15volt and the current is 2-5a. The cooling box material is covered with styrofoam, with a heat sink in the form of a heat sink fan. Variations are made on the amount of thermoelectric used. Data retrieval is done by installing a voltmeter, ammeter and thermocouple in a predetermined position then each measuring instrument will display the data. The data is then processed using the Microsoft Excel program which can produce graphs. With the form of a graph, discussion and conclusion can be done easily